Enhancement of the Raman Scattering and the Third-Harmonic Generation in Silicon Nanowires - Golovan, L.A.; Bunkov, K.V.; Gonchar, K.A.; Timoshenko, V.Yu.; Osminkina, L.A.; Petrov, D.V.; Marshov, V.S.; Sivakov, V.A.; Kulmas, M.N. (ALT Proceedings, 2026)
We studied features of Raman scattering and the third-harmonic generation in silicon nanowire (SiNW) ensembles formed by means of chemical etching of crystalline silicon (c-Si) wafers with preliminary deposited silver nanoparticles in hydrofluoric acid. The c-Si wafers of different crystallographic orientations and doping levels were used, which results in variations of the formed nanostructure size and degree of order. For the excitation at 1064 nm the ratio of Raman scattering signals for SiNWs and those for initial c-Si wafer ranges from 2 to 5, whereas for shorter wavelengths the ratio increases for more ordered arrays of SiNWs of greater diameter and decreases for less ordered SiNW structures. The TH signals in SiNW ensembles demonstrate both fall and one- or two-orders-of-magnitude rise in comparison with c-Si depending on the structure of the SiNW ensemble. The obtained results are explained by the effect of partial light localization in SiNW ensembles.